Fiber Bragg gratings inscriptions in multimode fiber using 800 nm femtosecond laser for high-temperature strain measurement. (1st August 2017) - Yang, Tingting; Qiao, Xueguang; Rong, Qiangzhou; Bao, Weijia
Highlights: Three FBGs inscriptions are achieved at different positions of MMF core cross-section by femtosecond laser. Micro-strain sensitivities of the sensor are different at different temperature. An analysis on the strain sensitivity versus temperature is performed. Abstract: A short fiber Bragg grating (FBG) is successfully written in a multimode fiber (MMF) with core and cladding diameters of 50 μm and 125 μm using 800 nm femtosecond laser side-illumination technique. Three-type grating inscriptions can be realized at the different positions over the core of MMF by moving the focal-line position of laser beam. Both fundamental mode and higher-order modes of MMF are excited at the core-mismatch junction, resulting in two well-defined resonances in transmission. The strain measurement with a single core resonance mode is demonstrated experimentally at the ultra-high temperature. The result indicates that the strain sensitivity improved to 5.24 pm/µε at the temperature of 600–900 °C, making it as a good candidate for the strain measurement at the high temperature environments.